2012
DOI: 10.1111/apt.12132
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: comparison of two everolimus dosing schedules in patients with advanced hepatocellular carcinoma

Abstract: SUMMARY BackgroundDeregulation of mammalian target of rapamycin (mTOR) signalling is common in human hepatocellular carcinoma (HCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…Data from phase 1 and 2 studies showed a stabilization of HCC progression with everolimus (72,73). As yet there are no clinical studies to establish its true role.…”
Section: Mammalian Target Of Rapamycin Inhibitors (Mtor)mentioning
confidence: 99%
“…Data from phase 1 and 2 studies showed a stabilization of HCC progression with everolimus (72,73). As yet there are no clinical studies to establish its true role.…”
Section: Mammalian Target Of Rapamycin Inhibitors (Mtor)mentioning
confidence: 99%
“…Data from clinical trials on a variety of molecular targeted therapies for advanced HCC are shown in table 1[3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]. …”
Section: Clinical Trials Of Molecular Targeted Therapy For Advanced Hccmentioning
confidence: 99%
“…The recommended phase II dose of everolimus was 7.5 or 10 mg per day for monotherapy in HCC patients [28,29]. A phase III, randomized, placebo-controlled trial testing the efficacy of everolimus 7.5 mg po qd after sorafenib failure has completed patient recruitment, and the results will be available by the end of 2013.…”
Section: Clinical Trials Of Molecular Targeted Therapy For Advanced Hccmentioning
confidence: 99%
“…Currently, everolimus has proven anticancer activity in advanced renal cell carcinoma following VEGFr-TKIs [43], in advanced, progressive neuroendocrine tumors [44], and, in combination with exemestane, in advanced hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer that progressed on prior hormonal therapy [45]. Data regarding the safety and efficacy of everolimus in HCC come from two prospective studies [46,47]. In a phase I/II trial conducted in 28 patients with advanced HCC, 20 (71%) of whom had received previous systemic therapy, no dose-limiting toxicities were experienced and everolimus was generally well tolerated at a dose of 10 mg/day [46].…”
Section: Mtor Inhibition In Unresectable Advanced Hccmentioning
confidence: 99%
“…A phase I dose-finding study on everolimus for advanced HCC evaluated both daily (n =21) and weekly (n =18) dosing schedules [47]. Based on the observed dose-limiting toxicities of hyperbilirubinemia, alanine aminotransferase elevation, thrombocytopenia, infection, diarrhea, rectal bleeding, and cardiac ischemia, the maximum tolerated doses were determined to be 70 mg/week and 7.5 mg/day.…”
Section: Mtor Inhibition In Unresectable Advanced Hccmentioning
confidence: 99%